Knowledge management model for educational quality through university extension (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
This essay aims to build a theoretical approach of a model of knowledge management for the quality of university education through the University extension. The study begins with a documentary review of the theoretical foundations of management knowledge, organizational culture, quality of education and University extension. Research supported in an epistemological sense positivist, that made it possible to sustain the ontological realism, objectivity and discover how the knowledge management for a quality education through the University extension. The conceptualization that was used in this test allowed highlight explanations of the reality of the situation being studied, making it clear, that the model proposed prevails a theory which based condition sinecuanon for the formulation of an archetype. The theoretical model was established by three large components (knowledge management, quality education and University extension) that are interconnected to form a whole that presents properties and characteristics are not in any of its components in an isolated way. Therefore, any action to change in any component, will probably produce changes in all.
Keywords: model; management knowledge; quality of education; university extension